Crouching Tiger, Hidden Dragon : What Are the Consequences of China's WTO Entry for India's Trade? (IMF Working Papers; Working Paper ;, 2005)
One of the most significant recent developments in world trade has been the entry of China into the World Trade Organization (WTO). This paper examines the implications of China's WTO accession for India's trade, using both econometrics and computable general equilibrium (CGE) models. The paper analyzes how India stands to lose or gain from China's WTO entry in terms of both the direct and competitive channels.